Perbedaan Self Control Mahasiswa Dalam Belajar Ditinjau Dari Perlakuan Orang Tua Dan Jenis Kelamin - Rofiqa Duri; Zain, Arifin; Jarnawi, Jarnawi; Muttaqin, Reza (Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2024)
This research focuses on the lack of self-regulation in students during the learning process. Students who have good self-control skills will be able to solve the problems they face. Parental treatment and gender are important factors in student self-control. The level of self-control demonstrated by individuals can vary based on their gender and the way they were raised by their parents. Variations in student self-control are shaped by many internal and external influences. Students' self-control allows them to effectively manage and regulate their behavior in the learning process, preventing them from giving in to temptation and engaging in negative or deviant actions. This research examines parental treatment and gender to analyze student self-control. This ex post facto research used a 3 x 2 factorial design. Students of the Islamic Guidance and Counseling Study Program, Faculty of Da'wah and Communication, UIN Ar-raniry were the research population. Proportional random sampling was used. The instrument used was a questionnaire with validity test results > 0.304 and reliability test results for the self-control instrument were 0.903 and the parental treatment variable was 0.933. Analysis of variance (ANOVA) was used. The results of research on the interaction between the variables parental treatment and gender, the Fcount value obtained was 0.238, so it can be concluded that Fcount < Ftable, in accordance with the criteria for hypothesis testing via Anava, so this shows there is no interaction between parental treatment and gender. Gender in influencing students' self-control in learning.